The Role of Village Governance in Strengthening Legal Awareness in Indonesian Local Communities - Muhammad Bagus Sanjaya (JUSTISIA GLOBAL EDUKASI, 2026)
Village governance plays a strategic role in promoting legal awareness and strengthening the rule of law within local communities in Indonesia. As the closest level of government to citizens, village institutions possess significant potential to facilitate legal education, encourage civic participation, and support access to public services. This study examines the role of village governance in enhancing legal awareness among Indonesian local communities through a sociolegal perspective. Using qualitative sociolegal methods, the research analyzes the interaction between local governance structures, community participation, and legal literacy initiatives. The findings indicate that village governments contribute substantially to disseminating legal information, mediating local disputes, and fostering compliance with legal norms. However, variations in institutional capacity, educational resources, and community engagement affect the effectiveness of legal awareness programs across different regions. The study reveals that legal awareness is influenced not only by formal legal knowledge but also by social trust, cultural values, and perceptions of institutional legitimacy. Community-based legal education programs, participatory governance mechanisms, and collaboration with civil society organizations can significantly strengthen public understanding of legal rights and responsibilities. Furthermore, the integration of digital communication technologies creates new opportunities for expanding legal outreach and civic engagement at the village level. The research argues that effective village governance serves as an important bridge between formal legal institutions and local communities. The study concludes that strengthening village governance capacity is essential for promoting legal empowerment, social inclusion, and sustainable legal development in Indonesia. These findings highlight the importance of local governance in advancing legal consciousness and community resilience.